76=58+9d

Simple and best practice solution for 76=58+9d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 76=58+9d equation:


Simplifying
76 = 58 + 9d

Solving
76 = 58 + 9d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-9d' to each side of the equation.
76 + -9d = 58 + 9d + -9d

Combine like terms: 9d + -9d = 0
76 + -9d = 58 + 0
76 + -9d = 58

Add '-76' to each side of the equation.
76 + -76 + -9d = 58 + -76

Combine like terms: 76 + -76 = 0
0 + -9d = 58 + -76
-9d = 58 + -76

Combine like terms: 58 + -76 = -18
-9d = -18

Divide each side by '-9'.
d = 2

Simplifying
d = 2

See similar equations:

| 4(a-2)=16 | | (28y-1274)/2y=1 | | 2(y+2)=7 | | p-7=7 | | (2y-91)/2y=1/14 | | 2*14=21 | | 9v+17=-6 | | r/2-39=41 | | 2k-9=-15 | | 0.005439x^2-0.37x=0 | | 1/2(t+4)=13 | | 1+6lnx=0 | | 17x+12=8x | | x^2+12x+33=1 | | 7-4p=2p-5 | | f(1)=x^2+12x+33 | | f(x)=x^2+12x+33 | | -m/42=5 | | S=4nr+2nrh | | S=4nr+2nr | | (9+x)(x-6)=0 | | 2=10+7/-3 | | 5x+1=10+x | | 14r^2-23r+8=0 | | 32+4s-s^2=0 | | 2a^2-13ab+20b^2=0 | | 9x-12y+9=19x-15y+10 | | 39-9n=-6n | | (16X+9Y-7Z)+(-8X-5Y)= | | 3g-8=fg-20 | | Y=13-9x | | 2e^2x-1=5 |

Equations solver categories